PENGEMBANGAN MEDIA PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI BERBASIS MULTIMEDIA BAGI GURU-GURU SEKOLAH DASAR DI DESA KINTAMANI BANGLI - N.M.A.E.D. Wirastuti; I.G.A.K.D.D. Hartawan; I.M.A. Suyadnya; D.C. Khrisne (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Along with the advancement of science and technology, all teachers especially primary school teachers areexpected to have the ability in the field of information and communication technology (ICT). So that teacherscan teach using ICT-based learning media. By using multimedia learning model, teachers will be able to doteaching more interactive, fun, and motivate learners to be more active. The goal of this program is toimprove the ability and competence of teachers in Elementary School (SD) Imbas in Kintamani Village areasin creating multimedia-based ICT learning media. In this community service activities, it is given counselingand training about the introduction of the Internet and the development of multimedia-based ICT learningmedia using Microsoft PowerPoint, create teaching materials in PDF format, create teaching materials inimage display (JPEG) and apply teaching materials in activities learning in the class. The purpose of this activity is the participants understand of the importance in using ICT for supporting learning and teachingactivities multimedia-based learning media. Participants also understand of how to create learning materialsin PowerPoints format, create files in the form of .pdf, and generate. JPG files. Teachers will also be trainedon how to enrich multimedia-based learning materials using internet access.